1996
DOI: 10.2503/jjshs.64.741
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium rhizogenes mediaredTransformation of Kiwifruit (Actinidia deliciosa) by Direct Formation of Adventitious Buds.

Abstract: Agrobacterium rhizogenes-mediated transformation of kiwifruit (Actinidia deliciosa (A. Chev.) C. F. Liang and A. R. Ferguson) was achieved by direct formation of adventitious buds on infected petioles. Leaf explants of four cultivars (cv. 'Hayward', 'Matsua', 'Abbott' , and 'Bruno') were co-cultivated with four Japanese wild strains of A. rhizogenes (ArM 123, IFO 14555, A5 and A13). ArM 123 inoculations of the cultivars 'Hayward' and 'Bruno' resulted in 30.6 % and 16.7 % of adventitious buds formation respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Phenotype alterations were noted in some plants (Pe Ârez-Molphe-Balch and Ochoa-Alejo, 1998). In kiwifruit, Yamakawa and Chen (1996) achieved A. rhizogenes-mediated transformation by direct formation of adventitious buds on infected petioles. A mixture of normal and Ri phenotype plants were obtained.…”
Section: Normal Phenotypementioning
confidence: 97%
“…Phenotype alterations were noted in some plants (Pe Ârez-Molphe-Balch and Ochoa-Alejo, 1998). In kiwifruit, Yamakawa and Chen (1996) achieved A. rhizogenes-mediated transformation by direct formation of adventitious buds on infected petioles. A mixture of normal and Ri phenotype plants were obtained.…”
Section: Normal Phenotypementioning
confidence: 97%
“…Previous studies have shown that A. rhizogenes NIASE1724 and ArM123 may also apply to kiwifruit A. deliciosa A. Chev. (Yazawa et al 1995 ; Yamakawa and Chen 1996 ) and their efficiency of hairy root induction ranged from 2.5 to 30%, respectively. In this study, we used a different strain K599 to infect ‘Hongyang’ and revealed that about 50% of explants produced hairy roots and each explant could generate an average of 3.3 hairy roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cut-dip-budding delivery system using A. rhizogenes achieves effective transformation and gene editing without tissue culture and sterile conditions in the plant species with root-suckering ability (Cao et al 2023 ). Previous studies have shown that A. rhizogenes may also apply to kiwifruit (Yazawa et al 1995 ; Yamakawa and Chen 1996 ), but few studies utilizing hairy root transformation in kiwifruit have been reported, possibly because of its low transformation and regeneration efficiency.…”
Section: Introductionmentioning
confidence: 99%